TO STUDY THE EXTENT TEACHERS, ASSESS AND MEET LEARNING INTENTION AND INTEREST OF LEARNERS - Shahina Shabbir; Shahid Raza; Aks-E-Noor (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This is a prerequisite of the productive teaching-learning process to explore learners to find out their needs, their intention map of learning, and interest so that they can be accommodated in the teaching-learning process as per their terms. So the intelligence of learners is explored through different psychological interventions by teachers. To explore the learning intention of learners also requires considering and finding individual needs of learners, individual differences, learners' interests, readiness, and engagement in work. The purpose of this study was to explore the role of teachers to assess the mental abilities, interests, learning profile, readiness, and engagement of learners. The target population was the teachers of five districts of # south Punjab. Data were gathered through a questionnaire from teachers. Participants were more or less agreed that the proper assessment of the learning intention of leaner will help the teacher to address the individual needs of leaner.. The results reveal that pre-assessment of learners' interests plays a positive role in the teaching learning process.